Polymerase chain reaction-driven detection of Leptospira spp. in urban rat populations of Surabaya, Indonesia - Edza Aria, Wikurendra; Josfirin Uding, Rangga; Akas Yekti Pulih, Asih; Teguh Suranta, Sinulingga (Elsevier Ltd, 2025)
Objectives: Leptospirosis is a zoonotic disease caused by Leptospira spp., with rodents as the main reservoir. This study aims to detect Leptospira spp. in the urban rat population in Surabaya using the polymerase chain reaction (PCR) method and analyze its phylogenetic relationship. Methods: This laboratory-based surveillance study used a molecular approach to detect Leptospira spp. in the urban rat population from Genteng Village, Surabaya using PCR for detection and subsequent phylogenetic analysis of the positive isolates based on the partial lipL32 gene sequence. A total of 30 rat traps were set up, and 26 rats were successfully captured. Results: The PCR results showed that 22 of 25 Rattus norvegicus (88 %) were positive for Leptospira spp., whereas the single Rattus tanezumi and three other Rattus norvegicus were negative. With a prevalence rate of 84.6 %, these findings indicate a high risk of leptospirosis transmission in Surabaya. Phylogenetic analysis revealed that Leptospira DNA from Rattus norvegicus are closely related to Leptospira interrogans, a species known to be pathogenic to humans. Conclusions: These results strengthen the evidence that Rattus norvegicus plays a major role as a vector in the spread of leptospirosis in urban environments. Therefore, mitigation efforts, such as rodent population control, improved environmental hygiene, and community education, are needed to reduce the risk of leptospirosis infection.